Impaired coenzyme A synthesis in fission yeast causes defective mitosis, quiescence-exit failure, histone hypoacetylation and fragile DNA. Issue 9 (September 2012) - Nakamura, Takahiro; Pluskal, Tomáš; Nakaseko, Yukinobu; Yanagida, Mitsuhiro
Abstract : Biosynthesis of coenzyme A (CoA) requires a five-step process using pantothenate and cysteine in the fission yeast Schizosaccharomyces pombe . CoA contains a thiol (SH) group, which reacts with carboxylic acid to form thioesters, giving rise to acyl-activated CoAs such as acetyl-CoA. Acetyl-CoA is essential for energy metabolism and protein acetylation, and, in higher eukaryotes, for the production of neurotransmitters. We isolated a novel S. pombe temperature-sensitive strain ppc1-537 mutated in the catalytic region of phosphopantothenoylcysteine synthetase (designated Ppc1), which is essential for CoA synthesis. The mutant becomes auxotrophic to pantothenate at permissive temperature, displaying greatly decreased levels of CoA, acetyl-CoA and histone acetylation. Moreover, ppc1-537 mutant cells failed to restore proliferation from quiescence. Ppc1 is thus the product of a super-housekeeping gene. The ppc1-537 mutant showed combined synthetic lethal defects with five of six histone deacetylase mutants, whereas sir2 deletion exceptionally rescued the ppc1-537 phenotype. In synchronous cultures, ppc1-537 cells can proceed to the S phase, but lose viability during mitosis failing in sister centromere/kinetochore segregation and nuclear division. Additionally, double-strand break repair is defective in the ppc1-537 mutant, producing fragile broken DNA, probably owing to diminished histone acetylation. The CoA-supported metabolism thus controls the state of chromosome DNA.